RESEARCHES ON THE CAPACITY OF MARKETING AGRICULTURAL CROP PRODUCTION IN THE SOUTH-WEST OLTENIA REGION - Ana Ruxandra MICU; Valentina TUDOR; Eduard Alexandru DUMITRU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Further, the vegetal sector encounters serious problems and is often dependent on a number of factors such as climate, whether the crops are irrigated or not. This factors can make a difference between gain and loss. There are other factors such as economic factors where this market is extremely volatile, but also a number of other factors described in this paper. This case study was carried out on a sample of 60 farms with a vegetal profile showing the level of this region compared to the national average, identifying the main strengths and weaknesses that farmers in this region have. Account should also be taken of the marketing capacity of agricultural crop production. Interviewing the representatives of 60 agricultural crops we could analyse a number of relevant issues for this sector through which we can contribute with a series of solutions and recommendations.